STRATEGI BALAI KONSERVASI SUMBER DAYA ALAM (BKSDA) REJANG LEBONG DALAM MEMPROMOSIKAN TAMAN WISATA ALAM (TWA) BUKIT KABA - Sari, Winda (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2024)
Bukit Kaba Nature Tourism Park in Rejang Lebong Regency is a promising tourist destination and has great potential. Bengkulu BKSDA is responsible for monitoring, researching, protecting and managing ecosystems and rare or endangered species in the area. Through this research, it is also hoped that it can Concrete recommendations emerge that can be implemented by BKSDA and related parties to increase the effectiveness of communication strategies in promoting this extraordinary tourist destination. The research uses qualitative methods which focus on in-depth understanding of meaning, perception and human interaction, and generalizing utilization data. Qualitative methods in research can produce a more comprehensive examination of a phenomenon, by conducting interviews, observations, or document analysis. This research uses Kotrel & Armstrong's 4P Marketing Mix theory implemented by BKSDA and BumDes Sumber Urip that: 1. The product in this research is not only Kaba Hill but there is also the blue crater, the steps of Gajah Hill and the Kaba Hill Courtyard Lake. 2 The price for entering the Kaba Hill Nature Tourism Park (TWA) area is still quite cheap and affordable, so that climbers who climb Kaba Hill do not feel at a loss. 3 Places, the Nature Tourism Park itself is in Sumber Urip Village. Riejang Lebong Regency, Biengkulu. From the city of Bengkulu, it only takes 2 hours to get to Sumber Urip Village. 4 Promotion, the promotion that has been carried out by BKSDA has been very optimal by collaborating with BumDes Sumber Urip, however due to inadequate facilities this strategy has not been maximized Keywords: Communication Strategy, BKSDA, Promotion